NMDA receptors amplify mossy fiber synaptic inputs at frequencies up to at least 750 Hz in cerebellar granule cells. Issue 7 (7th March 2016) - Baade, Carolin; Byczkowicz, Niklas; Hallermann, Stefan
ABSTRACT: Neuronal integration of high‐frequency signals is important for rapid information processing. Cerebellar mossy fiber axons (MFs) can fire action potentials (APs) at frequencies of more than one kilohertz. However, it is unclear whether and how the postsynaptic cerebellar granule cells (GCs) are able to process these high‐frequency MF inputs. Here, we measured AP firing in GCs during high‐frequency MF stimulation and show that GC firing frequency increased non‐linearly when MF stimulation frequency was increased from 100 to 750 Hz. To investigate the mechanisms enabling such high‐frequency signaling, we analyzed the role of N ‐methyl‐d ‐aspartate receptors (NMDARs), which have been implicated in synaptic signaling at lower frequencies. Application of D‐2‐amino‐5‐phosphonopentanoic acid (APV), a potent inhibitor of NMDARs, strongly impaired the GC firing frequency during high‐frequency MF stimulation. APV had no significant effect on single excitatory postsynaptic potentials (EPSPs) or currents (EPSCs) evoked at 1 Hz at resting membrane potentials. However, the time course of EPSCs evoked at 1 Hz at depolarized potentials or following high‐frequency MF stimulation was accelerated by APV. Thus, our results show that NMDAR‐mediated currents amplify high‐frequency MF inputs by prolonging the time courses of synaptic inputs, thereby causing greater synaptic summation of inputs. Hence, NMDARs support the integration of MF synaptic input at frequencies up to at least 750 Hz.Synapse 70:269–276, 2016. © 2016 Wiley Periodicals, Inc. Abstract : Using whole‐cell patch‐clamp recordings from cerebellar granule cells (GCs), we show that GCs can process mossy fiber (MF) input frequencies up to at least 750 Hz. NMDA receptors amplify the integration of these high frequencies, but do not affect single postsynaptic potentials. Thus, NMDA receptors enable signaling at exceptional high frequencies.